P378 Immunisation practices for hepatitis B and response to vaccination in Greek patients with inflammatory bowel disease. (16th January 2018) - Kalogera, D; Siakavellas, S; Zambeli, E; Tsironi, E; Tzouvala, M; Moschovis, D; Kostas, A; Axiaris, G; Kourkoutas, E; Filippakou, K; Vlachogiannakos, J; Michopoulos, S; et al.
Abstract: Background: Low vaccination rates against hepatitis B virus(HBV) and sub-optimal response to vaccination are reported in patients with IBD. We initiated a multi-centre study in the metropolitan area of Athens, to assess: a)the percentage of IBD patients with protective anti-HBs levels and b)the response to vaccination. Methods: We reviewed the clinical records of all IBD patients with regular follow-up at 4 tertiary hospitals in Athens. All patients were tested for HBsAg, anti-HBs and anti-HBc antibodies. Patients with negative tests for both HBsAg and anti-HBc were managed as follows: a)negative anti-HBs without history of vaccination: 3-dose vaccination(0, 1, 6mo) with 20μg b)history of vaccination: anti-HBs levels >100 IU/l: annual follow-up of anti-HBs levels; anti-HBs 10–100 IU/l, 1–3 20μg doses with anti-HBs measurement after each dose; undetectable anti-HBs, 1–3 20μg doses with anti-HBs measurement after each dose. Vaccination was considered complete when anti-HBs>100 IU/l were detected. In patients with negative anti-HBs levels after 3x20μg doses, vaccination was repeated with a double dose(40μg) with anti-HBs measurement after each dose. Results: Our study population consists of 686 IBD patients. Among those, 575 patients had recent HBV serology(84%). In our cohort we identified 8 cases of chronic HBV infection(HBsAg+) and 38 patients with previous exposure to HBV(HBsAg-, anti-HBc+). Protective immunity due to previous vaccination(HBsAg-, anti-HBc-, anti-HBs+>100 iu/l) was detected in 24%( n = 140). Sub-optimal anti-HBs levels were seen in 12%( n = 70). The majority of patients were negative for all three markers, indicating lack of effective vaccination( n = 319, 56%). Vaccination has been commenced in 243 patients. 206 patients completed their regimens. Response has been assessed in 177 patients: 106(60%) demonstrated sufficient response while 71 failed to develop immunity to HBV. Among non-responders, 39 received repeat vaccination, with 22 having achieved protective anti-HBs levels and 17 failing to respond again. There was a significant correlation between "low-tier"(only 5-ASA or no treatment) therapy at time of vaccination and successful response ( p = 0.015). There was also strong association ( p < 0.001) between age and presence of protective immunity, probably due to the application of HBV vaccination in the last 2 decades in Greece. Conclusions: A significant percentage of Greek IBD patients lack protective immunity against HBV. Classical vaccination regimen often fails to induce adequate levels of anti-HBs antibodies especially in cases that are receiving "high-tier" treatment (immunomodulation and/or immunosuppression). Increased awareness, intensified vaccination protocols and frequent testing of response may be required in this population.